Relationship between Pocket Money for Food Purchases and Fast Food Consumption Frequency among Nutrition Students - Ulfi Retno Palupi; Setyaningrum Rahmawaty (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Students tend to prefer fast foods that contain high energy and fat, despite their awareness of the health issues related to this habit. However, data on the influence of pocket money on fast food consumption among nutrition students remain limited. This study aimed to determine the relationship between pocket money for food and the frequency of fast food consumption among nutrition students. An online survey on university students’ eating habits was conducted through Google Forms between June and July 2022 by involving 319 nutrition students at the Department of Nutrition Science, Universitas Muhammadiyah Surakarta (UMS). Data were collected using a pocket money questionnaire and a validated UMS students’ eating habits questionnaire. Most students (60.2%) received pocket money for food from their parents, averaging below IDR 35,000.00 per day. Taste (54.9%) was the primary factor in food selection, and 59.9% of students were categorized as rarely consuming fast food. There was no correlation between the pocket money for buying foods and the frequency of fast food consumption among nutrition students at UMS (Chi-Square test; p = 0.100). Future research should explore taste thresholds across different fast food types to establish a healthy fast food policy.